Effectiveness of Financial Management in Traditional Snack Businesses (Home Industry Study in Makassar City) - Sulfati, Andi; Rapanna, Patta; Sukarno, Zulfikry (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The results of the study show that effective and efficient financial management is critical to the success of the traditional hawker home industry in Makassar City. Measures such as separating personal and business finances, developing a clear budget, and consistently monitoring cash flow help ensure business stability and growth. The use of financial technology facilitates financial recording and analysis, while efficient raw material stock management can reduce wastage. In addition, maintaining an emergency fund and conducting regular financial evaluations help anticipate risks and improve efficiency. These strategies, if implemented with discipline, will support business sustainability and growth amidst competition.